Growth performance of Eucalyptus clones under varying moisture levels - Sandhu, Navneet Kaur; Dhillon, G.P.S.; Brar, Ajmer Singh (Indian Journal of Agroforestry, 2020)
Eucalyptus species are known for capability to adapt to varying edaphic and moisture conditions, and is widely adopted by the progressive farmers in many parts of the country. Present study was conducted to assess the performance of five Eucalyptus clones under varying moisture levels. Four moisture levels viz., T1- submerged, T2- 30% moisture, T3- 25% moisture and T4- 15% moisture were applied to potted plants by following completely randomized design. T3 registered maximum values for growth traits i.e. plant height, collar diameter and number of branches, which were significantly higher than other treatments, except T2. T3 registered maximum values for biomass of branches and leaves as well as stem. Root biomass was recorded maximum in T2. Among studied clones, C-413 was found to be the best in terms of plant height; PE-13 and PE-11 in terms of collar diameter; and PE-12 in terms of biomass (branches, leaves and stem). Root biomass was recorded highest in PE-11. The adventitious root formation was also noticed in T1 and plants survived. The growth traits recorded the highest values at 25% moisture level (T3) and submerged conditions (T1) resulted in significant reduction in all the growth traits. Among the clones, PE-13 and PE-11 were found to be promising for biomass.